Analisis dan Perancangan Sistem Interactive Voice Response (IVR) Berbasis Openvxi Menggunakan Asterisk Pada Hotel Sahid Jaya - Kerta, Johan Muliadi; Jufri, Wike Apryanto; Nugroho, Alexander Aryo; Kurniawan, Andreas (Bina Nusantara University, 2010)
The purpose of this study is to provide a deep understanding of technology of IVR (Interactive Voice Recognition) in OpenVXI based network using Asterisk, that help Sahid Jaya hotel to streamline communication with the guests, improving service and employee effectiveness. The methodology used is analysis which is through surveys, observation and interviews with the company and the design method by designing system from the existing needs analysis. The results obtained from this research is Communication System based in IVR OpenVXI can be applied to existing VoIP network, without disrupting the existing network. Some existing services can be supported with this system usage. Conclusions can be drawn is the use of IVR in the network using VoIP technology is the best solution to overcome the problems and needs of the hospitality which one of these is limited information guest cna get that can provided by non-operators and for support service improvement.